The influence of policy advocacy and education on medical staff’s adaptation to diagnosis related groups payment reform in China: an analysis of the mediating effect of policy cognition - Ni, Zhi-Ying; Zhang, Bo-Kai; Song, Lei; Zang, Zhao-Yan; Yu, Hong (Frontiers in Public Health, 2024)
IntroductionIn recent years, China has been carrying out the Diagnosis Related Groups (DRGs) payment reform, which has an impact not only on payment methods and medical expenses, but also on the behaviors of medical staff. Some of these behaviors are unexpected by policymakers, such as turning away critically ill patients, disaggregating hospitalization costs, setting up disease groups with higher points, and so on. This phenomenon attracted the attention of some scholars, who put forward a few positive intervention measures, mainly including policy advocacy and system improvement. The scholars believed that the former was more feasible. However, there is a lack of research on the effects and influencing processes of these interventions. Therefore, this study aims to explore the influence of policy advocacy and education on medical staff’s adaptation to DRGs payment reform in China and the role of policy cognition in this process, in order to provide experiences for the smooth implementation and sustainable development of DRGs payment system.MethodsA questionnaire survey was conducted among 650 medical staff in five large general hospitals in Zhejiang Province, China, to understand their participation and feedback on policy advocacy and education, their adaptation to the current DRGs payment reform, and their cognition of relevant policies. After descriptive statistical analysis, partial correlation analysis, multiple linear regression models and bias correction Bootstrap sampling method were used to analyze the mediating effect of policy cognition factors.ResultsAll respondents had participated in organized collective policy advocacy and education activities in the past year, but the degree of satisfaction and recognition was not very high. 59.5 percent said their adaptation to the DRGs payment reform was average. Nearly half did not regularly pay attention to and participate in the management of the medical costs of patients with DRGs through compliance. And they had a low understanding of the specific rules of DRGs payment and did not form a high policy identity. The mediating effect values of policy cognition were 0.148, 0.152, 0.108, and 0.057, respectively, when the frequency and quality of policy advocacy and education influenced medical staff’s adaptive perception and adaptive behaviors.DiscussionThe organized collective policy advocacy and education can promote medical staff’s adaptation to DRGs payment reform by improving their policy cognition, and the action paths are diverse. Policymakers and hospital managers need pay attention to this phenomenon, and formulate demand-centered, value-oriented whole-process advocacy and education strategies while constantly improving the DRGs payment system. All of these provided a basis for further research and practice of positive intervention in DRGs payment reform.